Pemberdayaan Mahasiswa Melalui Program Mahasiswa Penting (Peduli Stunting) melalui Edukasi Pencegahan Stunting bagi Remaja di SMA/SMK Kota Medan - Widiya Nisa; Apriliani Apriliani (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Stunting remains a major public health issue in Indonesia. Preventive efforts should not only focus on toddlers but must also target adolescents as future parents, equipping them with adequate knowledge from an early age. This community service program aimed to empower university students through the "Mahasiswa Penting" (Students Who Care About Stunting) program, positioning them as educational agents to deliver stunting prevention information to high school and vocational school students in Medan City. The activity was conducted through training sessions for students as educational facilitators and the implementation of interactive health education sessions in schools. The materials covered included an introduction to stunting and the importance of adequate nutrition during adolescence. This program aimed to broaden adolescents' understanding of stunting, including its causes and how they can actively contribute to its prevention. It also sought to enhance students' communication skills in delivering health information. The activity was carried out in three high schools/vocational schools in Medan, reaching a total of 71 adolescent participants representing each school. The results showed an increase in knowledge, with the average score rising from 52.67 to 77.74. This indicates a significant improvement in adolescents' awareness of stunting and its risk factors. The program demonstrated that involving university students in stunting prevention can be an effective and sustainable promotive and preventive strategy. It is expected that this initiative can be expanded and replicated more broadly through cross-sectoral collaboration.Keywords: Stunting, University Students, Health Education, Adolescents